Nitrogen-Use Efficiency and Gene Expression Profiling of Tropical Maize Hybrids Selected for Contrasting Responses to Nitrogen Fertilizer (2012)
Low soil Nitrogen (N) and sub-optimal N fertilizer application result in low Grain Yield (GY) in maize. Genotypes with improved N-Use Efficiency (NUE) are beneficial to low-input agriculture. To facilitate the genetic improvement of tropical maize for NUE, information is required on the relative importance of N-Uptake Efficiency (NUpE) and N-Utilization Efficiency (NUtE), both components of NUE, the relationships among the gene networks in the developing cob tissue and agronomic traits under limited N. This study was undertaken to evaluate genetic variation for NUE and investigate gene responses in the developing maize cob under sub-optimal N fertilizer application. Fourteen tropical maize hybrids differing in GY under low-N conditions were grown at no-N (0 kg N/ha), low-N (30 kg N/ha), and high-N (90 kg N/ha) in a randomized complete block design with four replications from 2006 to 2008. Data collected on GY and its components, NUE, NUpE, NUtE, and N-related traits were analysed using ANOVA at p=0.05. Path analysis was carried out to capture the intricate relationships among traits related to GY and NUE. Microarray technique using Maize Oligonucleotide array slides containing ~57000 probes were used to identify differentially expressed genes in developing cob tissues harvested from three N-use efficient hybrids compared to an N-use inefficient reference hybrid. Differentially expressed genes were validated by quantitative Real Time Polymerase Chain Reaction (qRT-PCR). Genotype and Genotype × Nitrogen interaction were significant for GY and NUE-related traits. Mean GY across years was reduced by 76.5% at no-N and 35.4% at low-N. It varied from 2.0 to 3.2 Mg/ha at low-N and 3.3 to 4.4 Mg/ha at high-N. Number of kernels (KN) was the GY component most severely reduced under nitrogen stress. Nitrogen use efficiency, NUtE and NUpE increased by 61.4, 42.1 and 21.0% respectively from high-N to low-N. Grain yield was positively and significantly correlated with NUE, NUtE and NUpE at both low-N and high-N. Stover nitrogen content at silking and NUE had strong positive direct effects on GY under low-N and high-N. Both NUtE and NUpE had significant positive direct effects on NUE. The relative importance of NUpE and NUtE varied depending on genotype and environment. Four hybrids (4001/4008, KU1409/9613, KU1409/4008 and 4008/1808) produced similar above average GY at low-N and high-N but differed in their NUpE and NUtE. Gene expression profiling of developing cob tissues revealed that at low-N, 163 of the probes on the array showed differential expression across the test hybrids. Under low-N, the probe MZ00019244 corresponding to the L-asparaginase gene showed the strongest relative mRNA expression in the highest yielding hybrid (KU1409/9613). L-asparaginase mRNA expression level was positively and significantly correlated with GY, KN and NUtE. Genetic variation for nitrogen use efficiency and its components was present among the tropical hybrids. L-asparaginase mRNA expression would be a valuable tool for selecting maize genotypes with high nitrogen utilization efficiency and superior grain yield under low soil nitrogen